2020
DOI: 10.1007/s00406-020-01211-1
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of internet use among university students

Abstract: The last 2 decades have seen an increase in the number of reports of excessive internet use. Therefore, this study aimed to examine internet use among university students to gain more insight into the novel phenomenon of addictive internet use (AIU). Data were collected by the means of an online questionnaire sent to 4391 students. Approximately 10% of the 4391 students could be included in the statistical analysis. Of those 483 students, almost all (99.2%) used the internet, and a quarter (24.8%) showed AIU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…These findings were in harmony with a study conducted by Ibrahim et al (2016) in Egypt who reported that the students use the internet for playing games and attending YouTube less than half and less than two thirds respectively. These findings were disagreed with a study done by Adorjan et al (2021) in Germany who reported that the most common reason for using the internet was information searches, followed by random browsing. While only less than one quarter of the studied sample used the internet for online gaming.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings were in harmony with a study conducted by Ibrahim et al (2016) in Egypt who reported that the students use the internet for playing games and attending YouTube less than half and less than two thirds respectively. These findings were disagreed with a study done by Adorjan et al (2021) in Germany who reported that the most common reason for using the internet was information searches, followed by random browsing. While only less than one quarter of the studied sample used the internet for online gaming.…”
Section: Discussioncontrasting
confidence: 92%
“…The main distinction between a smartphone and a mobile phone is that, with the former, a user can access the internet, with all its features, and can download and execute programs 1,2 . In addition to e‐mail, instant messaging, and random browsing via the internet, social networking sites allow individuals to establish communication with others and share videos, photographs, and comments 3,4 . As a result, the popularity of these platforms is increasing in Turkey and worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…So, is SNS a "first-choice drug"? It may simply be the "front page of the internet" (Adorjan et al, 2021;Asrese & Muche, 2020;Lagorio-Chafkin, 2018;Organisation for Economic Cooperation & Development, 2019).…”
Section: Discussionmentioning
confidence: 99%